Ghuwai Cetik - Aris Tiano (Institut Seni Indonesia Yogyakarta, 2017)
Cetik is a traditional tool Lampung derived from Skala kingdom Brak Lampung West. Estimated to have existed since centuries 485sm. While the word comes from Lampung ghuwai which means create, make, do a job. Two words into ghuwai cetik, the musical instrument made of bamboo. Stylist interest by making cetik instrument is the source of the sound produced.Ghuwai cetik or how to make traditional musical instruments Lampung is an inspiration to stylists to be a theme in the musical composition. After finding inspiration in realizing further various stages such as stages of selection, cutting, tunings and finishing. The method used in the work of this musical composition using the Re-Interpretation and contemporary approach.Keywords: Ghuwai cetik, Process.